Morphological correlates of river velocity and reproductive development in an ornamented stream fish - Dugas, Matthew B; Franssen, Nathan R; Bastille, Maya O; Martin, Ryan A (Evolutionary ecology, 2016)
Adaptive phenotypic divergence can arise when environments vary in ways favoring alternative phenotypic optima. In aquatic habitats, the costs of locomotion are expected to increase with water velocity, generally favoring a more streamlined body and the reduction of traits that produce drag. However, because streamlining in fish may come at the cost of maneuverability, the net benefits of drag reduction can differ not only among habitats, but also among individuals (or classes of individuals) that rely on locomotion for different uses (e.g., males vs. females or adults vs. juveniles). We tested these predictions by exploring relationships among river velocity, body streamlining, ornamental fin size, and male reproductive condition in the steelcolor shiner (Cyprinella whipplei), a small-bodied North American cyprinid. Overall, males in peak reproductive condition (defined by the development of sexually dimorphic tubercles) had less streamlined bodies and larger ornamental fins than males in lower reproductive condition or individuals lacking these secondary sexual characters (females and immature males). There was a relationship between river velocity and body streamlining only for males in peak reproductive condition, but it was in the opposite direction of our predictions: these males were less streamlined in faster rivers. We found only weak support for the prediction that ornamental fin size would be negatively associated with river velocity. Overall, these results suggest either that drag is not an important selective pressure in these habitats, or that the sexual selection advantages of a deep body and large fin compensate any natural selection costs for C. whipplei males. This study highlights the often overlooked diversity of selective pressures acting on streamlining in fishes, and can offer novel insights and predictions allowing a more nuanced understanding of fish ecomorphology.